Physical and Sports Activity in Adolescent SPA Consumers - Tarqui Silva, Leonardo Eliecer (2017)
The present study shows the therapeutic approach based on physical and sports activities applied as reinforcer, channeler and behavioral modifier in conjunction with cognitive, socio-humanistic, spiritual, occupational, experiential and family therapies performed in adolescents using psychoactive substances (SPA) between Ages 14 to 17 years in the Therapeutic Community for Adolescent Males Hogar Crecer (CTHC), of the city of Cuenca - Ecuador; resulting in a reduction and channeling of aggressiveness levels, improvements in the area of socialization, self-esteem, academic performance and an adequate process of detoxification and direct incidence in the initial critical stage of abstinence. The results of the research are obtained through the application of clinical and sports psychological reagents; together provide the reports and diagnoses of weekly evolution of clinical staff during the 6 months of treatment in hospitalization modality administered in initial and subsequent periods of the psych educational process.